Control and optimization of defects in die casting of complicated right crankcase cover - Hong Xu; Wen-long Liu; Yu-peng Wang; Shi-zhong Ma; Chao Yuan; Hai-long Jia; Xiu-ming Cheng; Rui Wang (Journal of Materials Research and Technology)
The die-casting process of ADC12 aluminum alloy right crankcase cover was simulated based on AnyCasting software, and the influence of pouring temperature, initial mold temperature and injection speed on the filling and solidification process of ADC12 right crankcase cover casting was explored by orthogonal experiment method. The optimal process parameters were obtained through optimization, and the die-casting mold was designed. The program was verified in production. The results show that the porosity and shrinkage of the right crankcase cover are mainly concentrated in the thick wall part. The sequence of process parameters that affect the residual melt modulus is pouring temperature, initial mold temperature, and injection speed; The best combination of process parameters: pouring temperature is ∼680 °C, initial mold temperature is ∼200 °C, injection speed is ∼5 m/s. By analyzing the filling process and temperature field simulation results, the casting structure, mold structure and cooling system were optimized, and the process plan was improved. The production verification was carried out according to the optimized process plan. The casting quality is good and has no obvious defects, which meets the actual production needs.